Noninvasive Assessment of Exosome Pharmacokinetics In Vivo: A Review - Kim, Do Hee (Pharmaceutics, 2019)
Exosomes, intraluminal vesicles that contain informative DNA, RNA, proteins, and lipid membranes derived from the original donor cells, have recently been introduced to therapy and diagnosis. With their emergence as an alternative to cell therapy and having undergone clinical trials, proper analytical standards for evaluating their pharmacokinetics must now be established. Molecular imaging techniques such as fluorescence imaging, magnetic resonance imaging, and positron emission tomography (PET) are helpful to visualizing the absorption, distribution, metabolism, and excretion of exosomes. After exosomes labelled with a fluorescer or radioisotope are administered in vivo, they are differentially distributed according to the characteristics of each tissue or lesion, and real-time biodistribution of exosomes can be noninvasively monitored. Quantitative analysis of exosome concentration in biological fluid or tissue samples is also needed for the clinical application and industrialization of exosomes. In this review, we will discuss recent pharmacokinetic applications to exosomes, including labelling methods for in vivo imaging and analytical methods for quantifying exosomes, which will be helpful for evaluating pharmacokinetics of exosomes and improving exosome development and therapy.